APEC and preferential rules of origin : stumbling blocks for liberalization of trade. - JAMES, William E. (1997)
Presents a selective review of the state of economic thinking on issues surrounding rules of origin in the context of formation of regional integration initiatives. Considers the harmonisation of origin rules of sub-regional trade arrangements within APEC